2014
DOI: 10.3329/bjas.v43i1.19385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary exogenous phytase on laying performance of chicken at older ages

Abstract: A total of 48 Shaver-579 chicken layers aged between 85 to 94 weeks were reared in individual cages and given a basal diet amounting to 115g feed/bird/day. The basal diet fortified with 0.05, 0.10 or 0.15% RenaPhytase-400 constituted of 3 experimental diets to see the effects of exogenous phytase on egg production and egg quality. Results indicated that increasing level of exogenous phytase in diet almost linearly (p<0.05) increased egg production and feed conversion but did not affect egg quality. Providing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Liu et al (2005) showed increased egg production and egg mass of hens due to supplementation of antibiotic with water at the level of 20, 25, 30mg/kg BW. In this experiment egg production was increased 1.7% to 2.7% which is similar to Lucky (2010) and other authors. Rahman (2007) indicated different levels of antibiotic 15% and 30% had (P<0.05) influence on egg weig ht, whereas control had no improved egg mass production.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 77%
See 1 more Smart Citation
“…Liu et al (2005) showed increased egg production and egg mass of hens due to supplementation of antibiotic with water at the level of 20, 25, 30mg/kg BW. In this experiment egg production was increased 1.7% to 2.7% which is similar to Lucky (2010) and other authors. Rahman (2007) indicated different levels of antibiotic 15% and 30% had (P<0.05) influence on egg weig ht, whereas control had no improved egg mass production.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 77%
“…Discussion 4.1. Egg production (%) Lucky (2010) found providing 15and 20mg/kg body weight in the diet increased egg production by 2% to 5%, respectively. Mahanta JD et al (2009) found egg production and egg mass of hens (ISA brown layer aged 26 weeks) were improved by biocilin supplementation.…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 99%
“…However, phytase treatment at 1,200 FTU/kg had the same feed formulation as 300 FTU/kg but showed significantly lower colour L vs. PC, which might indicate that the effect of phytase on egg colour was more related to energy balance than corn inclusion levels. Other studies did not find significant differences in albumen index, yolk index, yolk percent or yolk colour with phytase supplementation (Jalal and Scheideler, 2001, Park et al, 2009, Lucky et al, 2014.…”
Section: Journal Of Applied Animal Nutritionmentioning
confidence: 83%
“…In addition, Ahmadi et al (2008) indicated that dietary phytase supplementation positively affected egg production, egg weight and feed intake of laying hens. Moreover, Lucky et al (2014) demonstrated that dietary phytase supplementation significantly improved egg production and feed conversion of aged laying hens.…”
Section: Resultsmentioning
confidence: 99%
“…Vet. Adv., 10 (12): 918-929, 2015Hughes et al, 2008Ziaei et al, 2009;Mohammed et al, 2010;Lucky et al, 2014) and eggshell quality (Lim et al, 2003;Hussein et al, 2006;Ziaei et al, 2009). Others failed to detect a beneficial effect for supplemental phytase on laying performance (Liebert et al, 2005;Al-Sharafat et al, 2009) or eggshell quality (Afsari et al, 2013;Lucky et al, 2014;Musilova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%